2010
DOI: 10.1016/j.jacc.2009.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic Cardiomyopathy

Abstract: Cirrhotic cardiomyopathy is a clinical syndrome in patients with liver cirrhosis characterized by an abnormal and blunted response to physiologic, pathologic, or pharmacologic stress but normal to increased cardiac output and contractility at rest. As many as 50% of cirrhotic patients undergoing liver transplantation show signs of cardiac dysfunction, and 7% to 21% of deaths after orthotopic liver transplantation result from overt heart failure. In this review, we critically evaluate the existing literature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
287
1
23

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(318 citation statements)
references
References 88 publications
(109 reference statements)
7
287
1
23
Order By: Relevance
“…Therefore, the clinical significance J Gastrointestin Liver Dis, September 2014 Vol. 23 No 3 of QT prolongation in cirrhosis still remains to be clarified [42]. Prolongation of the QT interval may also worsen after TIPS insertion both in cirrhotic and non-cirrhotic portal hypertensive patients.…”
Section: Qt Interval and Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the clinical significance J Gastrointestin Liver Dis, September 2014 Vol. 23 No 3 of QT prolongation in cirrhosis still remains to be clarified [42]. Prolongation of the QT interval may also worsen after TIPS insertion both in cirrhotic and non-cirrhotic portal hypertensive patients.…”
Section: Qt Interval and Dispersionmentioning
confidence: 99%
“…Most importantly, this condition should not be confused with alcoholic cardiomyopathy where the underlying mechanism responsible for the structural and functional cardiac abnormalities is well defined [2]. In contrast to alcoholic cardiac disease, in the case of CCM any well-defined underlying provoking factor(s) can be identified; however, sometimes iron overload or alcohol consumption may worsen the already hampered structural and functional condition of the myocardium [3]. In CCM, left and right ventricular contractile function may decrease resulting in an altered responsiveness to physical, physiological and pharmacological activity, leading to the characteristic symptoms of heart failure [4].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is independent of the etiology of cirrhosis and has been linked to an impairment of myocardial structure and function [77]. However, several studies have reported a wide spectrum of cardiovascular changes in cirrhotic patients, ranging from the sub-clinical stage of compensated liver disease to the typical hyperkinetic state of HS in decompensated disease [78,79].…”
Section: Cirrhotic Cardiomyopathymentioning
confidence: 99%
“…Patients with decompensated cirrhosis have been demonstrated to have elevated levels of the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and left ventricle (LV) diastolic dysfunction [5]. Cirrhotic cardiomyopathy is characterized by blunted contractile responsiveness to stress and/or altered diastolic relaxation with electrophysiological abnormalities in the absence of any other known cardiac disease, in patients with liver cirrhosis [6]. The pathogenetic mechanisms of cirrhotic cardiomyopathy include abnormalities in the beta-adrenergic signaling pathway, altered cardiomyocyte membrane fluidity, increased myocardial fibrosis, cardiomyocyte hypertrophy, and ion channel defects [1,7].…”
mentioning
confidence: 99%